EFFECTIVENESS OF FAMILY INFORMATION SYSTEM (SIGA) IN IMPROVING THE QUALITY OF FAMILY PLANNING SERVICES AT BKKBN JATIM - Dinda, Adinda Rahma Anisa; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of the Family Information System (FIS) in family planning data management at BKKBN East Java. This study also aims to evaluate the impact of using SIGA on operational efficiency and service quality in the field. Methods: This study used a descriptive qualitative approach with data collection through interviews, observation, and document analysis related to SIGA implemented in BKKBN East Java. The research subjects consisted of BKKBN officers and beneficiaries of the family planning program. The data collected was analyzed to describe how SIGA operates and affects service performance. Results: The results showed that the implementation of SIGA has successfully improved the efficiency of data recording and reporting of family planning activities. The system speeds up administrative processes and minimizes errors in data management. However, challenges related to the quality of technological infrastructure and limited internet networks in some areas are still an obstacle to the optimal implementation of SIGA. Novelty: This research offers a contribution to understanding the impact of information technology implementation in family planning data management in Indonesia. The success of SIGA in East Java can serve as a model for similar implementation in other regions, with a focus on improving infrastructure and developing features that are more in line with field needs.